Caribbean Report 22-02-1993 - Rowe, Yvette (anchor); Allen, Gary (correspondent); Miyares, Carlos (interviewee); Ramphal, Shridath (interviewee); Eckert, Timothy (correspondent); Hall, Wes (interviewee); Norton, Michael (correspondent) (The British Broadcasting Corporation, 1993)
The Opposition – the Jamaican Labour Party (the JLP) focuses its main attack on Prime Minister PJ Patterson. The launch provided an insight into the issues that the party plans to campaign on such as corruption and scandals. Edward Seaga says that he is ready – correspondent Gary Allen reports. Cuban research scientist - Dr. Carlos Miyares Cao has been doing research on the vitiligo disease for over a decade. He claims that he has a placenta based cure which he is offering to treat pop star Michael Jackson. The European Commission and central American countries agreed to broader cooperation despite differences over the EC banana import arrangements - the agreement was signed by representatives of the at a 9th Annual San Jose conference, San Salvador. Sir Shridath Ramphal - (Secretary General, Commonwealth Secretariat and Chairman of the West Indian Commission) doesn’t believe that CARICOM has given economic backing to the Windward Islands in its dispute over banana exports to Europe. Wes Hall, Barbados Sport and Tourism Minister believes that South Africa is a fertile ground for Caribbean tourism, and has set out to make key links between South Africa and the Caribbean by setting up meetings with Nelson Mandela, the South African Ministers of Tourism and Sport –- correspondent Timothy Eckert. Haiti’s Carnival has been on the decline for several years as a result of the country’s economic and political problems,the ferry disaster of the Neptune combined with the lack of financial backing of private businesses to the declining of the festivities – correspondent Michael Norton reports. Prince Charles paid a royal visit to Jamaica, but the Prince did not set foot on the island and the five hour visit was limited to the decks of the Royal Yacht Britannia.
Headlines with anchor Yvette Rowe (00:00 - 00:35).
1. The Opposition – the Jamaican Labour Party (the JLP) focuses its main attack on Prime Minister PJ Patterson. (00:36 - 02:51).
2. Cuban research scientist - Dr. Carlos Miyares Cao has been doing research on the vitiligo disease for over a decade, claims that he has a placenta based cure which he is offering to treat pop star Michael Jackson (02:52- 06:33).
3. The European Commission and central American countries agreed to broader cooperation despite differences over the EC banana import arrangements - the agreement was signed by representatives of the at a 9th Annual San Jose conference, San Salvador (06:34 -08:54).
Keywords: Jamaica-Politics and government.; Political campaigns—Jamaica--Elections.; Cuba--Medicine.; Cuba—Medicine--Research.; Bananas--Commerce--Windward Islands (West Indies).; Bananas—Commerce--Latin America.; Latin America--Economic conditions--Commerce.; European Union—Commerce--Latin America.; Bananas--Latin America--Politics and government.; European Union--Latin America--Politics and government.; Caribbean Community—Commerce--Caribbean Area.; European Union--Caribbean Area--Politics and government.; Tourism--South Africa.; Sports—South Africa.; Tourism--Caribbean Area.; Festivals--Haiti—20th century.; Haiti—Politics and government.; Haiti—Social conditions.; Shipwrecks—Haiti--20th century.; Natural disasters--Haiti.; Jamaica; Royal family--politics and government.; Politics and government—Janaica.